Histamine and Skin Barrier: Are Histamine Antagonists Useful for the Prevention or Treatment of Atopic Dermatitis? - De Benedetto, Anna (J Clin Med, 2015)
Atopic Dermatitis (AD), the most common chronic inflammatory skin disease, is characterized by an overactive immune response to a host of environmental allergens and dry, itchy skin. Over the past decade important discoveries have demonstrated that AD develops in part from genetic and/or acquired defects in the skin barrier. Histamine is an aminergic neurotransmitter involved in physiologic and pathologic processes such as pruritus, inflammation, and vascular leak. Enhanced histamine release has been observed in the skin of patients with AD and antihistamines are often prescribed for their sedating and anti-itch properties. Recent evidence suggests that histamine also inhibits the terminal differentiation of keratinocytes and impairs the skin barrier, raising the question whether histamine might play a role in AD barrier impairment. This, coupled with the notion that histamine’s effects mediated through the recently identified histamine receptor H4R, may be important in allergic inflammation, has renewed interest in this mediator in allergic diseases. In this paper we summarize the current knowledge on histamine and histamine receptor antagonists in AD and skin barrier function.